The Role of Agricultural Sector in Explaining Poverty in Indonesia: A Study Case of West Kalimantan - Nasrun, M. Ali; Fariastuti, Fariastuti; Indra, Sukma (International Journal of Economics and Financial Issues, 2020)
Poverty has become a significant economic problem and set as a priority of the United Nations (UN) in its Sustainable Development Goals (SDGs) program. Likewise, it remains a problem in the province of West Kalimantan, Indonesia, with its underprivileged population amounted to 369,730 people or 7.3% of the population in Indonesia. Meanwhile, Indonesia’s agricultural sector is expected to fulfill some objectives, namely providing food and helping people get out of poverty. Therefore, this research aims to test the influence of output and labor absorption in the agricultural sector on the number of poor populations in West Kalimantan, Indonesia. It employed multiple regression to analyze panel data from 2008 to 2017 from the Indonesian and West Kalimantan’s National Statistical Bureau (BPS 2019). The research findings indicated that the output of the agricultural sector positively and significantly influences the number of people living in poverty. In contrast, labor absorption in the agriculture sector positively, yet insignificant, influences the number of people living in poverty in West Kalimantan. It might be caused by low productivity in the agricultural sector. Keywords: the agricultural sector, poverty, labor absorption JEL Classifications: B22, Q01, Q12 DOI: https://doi.org/10.32479/ijefi.10334